2D Materials: Tuning the Electronic and Photonic Properties of Monolayer MoS2 via In Situ Rhenium Substitutional Doping (Adv. Funct. Mater. 16/2018). (17th April 2018) - Zhang, Kehao; Bersch, Brian M.; Joshi, Jaydeep; Addou, Rafik; Cormier, Christopher R.; Zhang, Chenxi; Xu, Ke; Briggs, Natalie C.; Wang, Ke; Subramanian, Shruti; Cho, Kyeongjae; Fullerton‐Shirey, Susan; et al.
Abstract : In article number1706950, Joshua A. Robinson and co‐workers demonstrate in‐situ Re doping of synthetic monolayer MoS2 with ≈1 at% Re on r‐plane sapphire. Electronic measurements and density functional theory calculations show that 1 at% Re doping achieves nearly degenerate n‐type doping. Low‐temperature photoluminescence reveals a suppression of defect emission, resulting from the passivation of defects due to the presence of Re. Picture Credit: Donna Deng.